2017
DOI: 10.3389/fphar.2017.00340
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Strategy for Discovering a Therapeutic Drug for Alzheimer’s Disease and Its Target Molecule

Abstract: Natural medicines are attractive sources of leading compounds that can be used as interventions for neurodegenerative disorders. The complexity of their chemical components and undetermined bio-metabolism have greatly hindered both the use of natural medicines and the identification of their active constituents. Here, we report a systematic strategy for evaluating the bioactive candidates in natural medicines used for Alzheimer’s disease (AD). We found that Drynaria Rhizome could enhance memory function and am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
99
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 44 publications
1
99
2
1
Order By: Relevance
“…Apart from NAR, its 7-O-G derivative was reported to cross the BBB and exhibit possible CRMP-2 binding ability and anti-AD activities. [14] In other words, while NAR and NAR-7-O-G reportedly bind to CRMP-2, reduce phosphorylation and facilitate axonal growth, NAR-4-O-G did not show selective binding, despite being able to cross the BBB. These findings present an ample opportunity to comparatively investigate the structural implications of NAR and NAR-7-O-G binding to CRMP-2, coupled with the molecular basis of selectivity as common to both compounds ( Figure 1).…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Apart from NAR, its 7-O-G derivative was reported to cross the BBB and exhibit possible CRMP-2 binding ability and anti-AD activities. [14] In other words, while NAR and NAR-7-O-G reportedly bind to CRMP-2, reduce phosphorylation and facilitate axonal growth, NAR-4-O-G did not show selective binding, despite being able to cross the BBB. These findings present an ample opportunity to comparatively investigate the structural implications of NAR and NAR-7-O-G binding to CRMP-2, coupled with the molecular basis of selectivity as common to both compounds ( Figure 1).…”
Section: Introductionmentioning
confidence: 90%
“…Although the possible binding activities of NAR and NAR-7-O-G have been previously demonstrated, [14] the mechanisms by which they reduce CRMP-2 phosphorylation with respect to the elimination of AD pathologies remain a subject of investigation till date. In our previous study, as a possible mechanism, we revealed the systemic perturbations of Tyr479, a target CRMP-2 phosphorylation site in the H19 helix, upon the binding of NAR.…”
Section: Structural Distortion Of Target Phosphorylation Sitesmentioning
confidence: 99%
See 3 more Smart Citations